Psychopathic Traits and Victimization: What Mechanisms Mediate the Relationship? - Daigle, Leah E. (Criminal justice and behavior, 2020)
Psychopathy has been linked to a host of negative outcomes including victimization; yet, the mechanisms that may explain this relationship have not been identified. Using data from the Pathways to Desistance study, a longitudinal study of adolescents adjudicted for serious offenses (N = 1,354) who had been adjudicated in either Maricopa County, AZ, or Philadelphia County, PA, we examine several mechanisms that may mediate the relationship between psychopathy and violent victimization. A 1 SD increase in psychopathy increases the risk of victimization by about 9.3%, net of control variables. Psychopathy is linked to violent victimization through its significant influences on engagement in risky behaviors, moral disengagement, motivations to succeed, and expectations for the future. These findings are striking given that they identify factors such as cognition and engagement in risky behavior that may be suitable targets for change in prevention or intervention efforts.